(untitled) (Purbanchal University Health Journal, 2024)
Introduction: Children with asthenopia are found to have various binocular visual problems on clinical examination. Objective: To determine the accommodative amplitude, fusional vergence, vergence status and refractive status of pediatric patients who presented with symptoms of Asthenopia. Method: Total 820 pediatric patients who had complaints of asthenopia were enrolled in the study. Clinical examinations including visual acuity assessment, slit lamp biomicroscopy, retinoscopy and binocular vision assessment were done. Patients who required glasses were prescribed with glasses. Patients who needed exercises on Synoptophore were called for follow up and those requiring pencil-push up exercise, Hart chart rock exercises and other vision therapy were advised to do at home. Result: Eight hundred twenty subjects were enrolled in the study. Among them, 51.85% were female and 48.15% were male. The most common age group presenting with symptoms of asthenopia at the OPD was 11-16 yrs. The most common binocular disorder was fusional insufficiency. Conclusion: Asthenopia has been associated with deficiencies in fusional vergence, as well as issues with accommodative and convergence insufficiency and refractive errors. It can be inferred that both muscular and refractive factors contributing to asthenopia should not be overlooked, as they can significantly affect children’s overall physical and academic growth.